Continous flow multi-stage grinder (2011)
A continous flow multi-stage grinder for grinding grains and other applicable food products comprises of hopper(001) which recieves the grain or food item to be milled and channels it to the mill housing (002) to be milled in stages. The conveyor (003) carries the milled product from one stage on grinding to the next. contained in the mill housing at every stage are the grinding plates (004). The finally ground poduct comes out for collection through the discharge channel (005). Grinding is achieved by an arrangement of pulleys(006) and v-belts(007) driven by an electric motor (008). Motion is transmitted to the mill housing at the three grinding stages by the transmission shaft (009). The entire grinder and electric motor are supported on a frame (010) and base (011) respectively.